Effects of Labor Values on Subjective Well-Being: The Mediating Role of Altruistic Tendencies - Chao, Xiaomei; Gu, Yuliang (Frontiers in Psychology, 2021)
This study examined the mediating role of altruistic tendency in the association between labor values and subjective well-being (SWB). About 2,691 Chinese students (1,504 males and 1,187 females) completed the labor values scale (LVS), the Positive Affect and Negative Affect Scale, the Satisfaction With Life Scale, and the altruistic tendency scale. Results demonstrated that labor values were positively associated with life satisfaction and positive affect, while negatively with negative affect. The altruistic tendency was positively correlated with labor values, and positive affect, while negatively correlated with negative affect. Furthermore, altruistic tendency served as a mediator linking labor values and positive/negative affect. These results confirmed the relationship between labor values and SWB and revealed the mechanism of altruism tendency between the two.